The use of intellectual standards to assess the quality of students' argumentative writings - Nakrowi, Zain Syaifudin; Ansori, Dadang S.; Mulyati, Yeti; Setyaningsih, Yuliana (LITERA, 2023)
To comprehensively examine the quality of argumentative writing, it is important to integrate the aspects of structure and substance. This study seeks to foreground the application of Intellectual Standards (IS) as a core component of the argumentative writing process. The research aims to determine the quality of argumentation in terms of structure using the TAP Toulmin concept and substance using IS. The research participants were 80 high school students in Central Java, Indonesia. A mixed method approach with an exploratory sequential QUAL-quan design is adopted. The results show that the quality of the arguments in terms of structure and substance is in the low category. Structurally, 97.5% of students' written arguments ranged from 1.1 to 2.0 on a scale of 0.0-5.0. In substance, 81.25% of students' argumentation ability scores are in the range of 04.9 - 09.6 on a scale of 0.00-24.00. In addition, the findings show that the completeness of the structure influences the substance score. Furthermore, the results of this study can be used as a reference for teachers in teaching argument texts. Elements of warrant, backing, modal qualifier, and rebuttal must be emphasized in preparing argumentative texts.Keywords: Argumentative Texts, Structure and Substance of Arguments, Toulmin, Intellectual Standards